Identification of Salmonella Pathogenicity Island-2 Type III Secretion System Effectors Involved in Intramacrophage Replication of S. enterica Serovar Typhimurium: Implications for Rational Vaccine Design - Rita Figueira (American Society for Microbiology, 2013)
ABSTRACT Salmonella enterica serovars cause severe diseases in humans, such as gastroenteritis and typhoid fever. The development of systemic disease is dependent on a type III secretion system (T3SS) encoded by Salmonella pathogenicity island-2 (SPI-2). Translocation of effector proteins across the Salmonella-containing vacuole, via the SPI-2 T3SS, enables bacterial replication within host cells, including macrophages. Here, we investigated the contribution of these effectors to intramacrophage replication of Salmonella enterica serovar Typhimurium using Fluorescence Dilution, a dual-fluorescence tool which allows direct measurement of bacterial replication. Of 32 strains, each carrying single mutations in genes encoding effectors, 10 (lacking sifA, sseJ, sopD2, sseG, sseF, srfH, sseL, spvD, cigR, or steD) were attenuated in replication in mouse bone marrow-derived macrophages. The replication profiles of strains combining deletions in effector genes were also investigated: a strain lacking the genes sseG, sopD2, and srfH showed an increased replication defect compared to single-mutation strains and was very similar to SPI-2 T3SS-deficient bacteria with respect to its replication defect. This strain was substantially attenuated in virulence in vivo and yet retained intracellular vacuole integrity and a functional SPI-2 T3SS. Moreover, this strain was capable of SPI-2 T3SS-mediated delivery of a model antigen for major histocompatibility complex (MHC) class I-dependent T-cell activation. This work establishes a basis for the use of a poly-effector mutant strain as an attenuated vaccine carrier for delivery of heterologous antigens directly into the cytoplasm of host cells. IMPORTANCE Live attenuated strains of Salmonella enterica serotype Typhi have generated much interest in the search for improved vaccines against typhoid fever and as vaccine vectors for the delivery of heterologous antigens. A promising vaccine candidate is the ΔaroC ΔssaV S. Typhi strain, which owes its attenuation mainly to lack of a type III secretion system (SPI-2 T3SS). The SPI-2 T3SS is important for bacterial proliferation inside macrophages, but not all of the effectors involved in this process have been identified. Here, we show that 10 effectors of the related strain S. Typhimurium contribute to intracellular replication in macrophages. Moreover, we establish that a poly-effector mutant strain of S. Typhimurium can have a severe replication defect and maintain a functional SPI-2 T3SS, which can be exploited for delivery of heterologous antigens.